Eccentricity evolution of massive black hole binaries from formation to coalescence. Issue 4 (29th January 2022) - Gualandris, Alessia; Khan, Fazeel Mahmood; Bortolas, Elisa; Bonetti, Matteo; Sesana, Alberto; Berczik, Peter; Holley-Bockelmann, Kelly
ABSTRACT: Coalescing supermassive black hole binaries (BHBs) are expected to be the loudest sources of gravitational waves (GWs) in the Universe. Detection rates for ground or space-based detectors based on cosmological simulations and semi-analytic models are highly uncertain. A major difficulty stems from the necessity to model the BHB from the scale of the merger to that of inspiral. Of particular relevance to the GW merger time-scale is the binary eccentricity. Here, we present a self-consistent numerical study of the eccentricity of BHBs formed in massive gas-free mergers from the early stages of the merger to the hardening phase, followed by a semi-analytical model down to coalescence. We find that the early eccentricity of the unbound black hole pair is largely determined by the initial orbit. It systematically decreases during the dynamical friction phase. The eccentricity at binary formation is affected by stochasticity and noise owing to encounters with stars, but preserves a strong correlation with the initial orbital eccentricity. Binding of the black holes is a phase characterized by strong perturbations; and we present a quantitative definition of the time of binary formation. During hardening the eccentricity increases in minor mergers, unless the binary is approximately circular, but remains largely unchanged in major mergers, in agreement with predictions from semi-analytical models based on isotropic scattering experiments. Coalescence times due to hardening and GW emission in gas-poor non-rotating ellipticals are ≲ 0.5 Gyr for the large initial eccentricities (0.5 ≤ e ≤ 0.9) typical of galaxy mergers in cosmological simulations.